Why Customers Abandon Online Shopping Cart: A Study of Consumer Behavior on Shopee - Keken Bella Hendrawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine behavioral factors influencing cart abandonment among Shopee users in Indonesia, with particular emphasis on price sensitivity, price comparison behavior, perceived value, and price fairness perception. Cart abandonment represents a critical challenge in e-commerce, as it reflects the gap between purchase intention and transaction completion. This research employs a mixed-method approach by collecting primary data through an online survey of 200 active Shopee users, complemented by secondary data from industry reports and academic literature. The data were analyzed using descriptive statistics and thematic interpretation to provide a comprehensive understanding of consumer behavior. The findings indicate that price sensitivity significantly affects consumers' decisions to delay or cancel online purchases, especially when consumers encounter price discrepancies, additional costs, or more attractive offers on competing platforms. Furthermore, low perceived value and perceptions of price unfairness at the checkout stage strengthen the likelihood of cart abandonment. These results suggest that cart abandonment is not solely driven by technical or usability issues but is largely the outcome of rational value and price evaluations conducted by consumers during the final stage of the purchase process. This study contributes to the literature on digital consumer behavior by highlighting the dominant role of price-related perceptions in emerging e-commerce markets. Practically, the findings offer strategic insights for Shopee to enhance price transparency, perceived value, and checkout conversion rates in Indonesia's highly competitive and price-oriented e-commerce environment.